The Effect of Service Quality and Omnichannel Marketing on Customer Loyalty Through Customer Satisfaction on the Apple Brand in Medan City - Mey Ramayanti Tinambunan; Arlina Nurbaity Lubis; Fadli (Indonesian Journal Publisher, 2025)
This study aims to determine and analyze the effect of service quality and omnichannel marketing on customer loyalty through customer satisfaction with the Apple brand. This type of research is associative research using quantitative data. The population in this study was Apple product users at Ibox Plaza Medan Fair, Ibox Manhattan Times Square Medan, and Ibox Mall Deli Park, with a sample of 180 respondents. The sampling technique used was purposive sampling with the criteria of respondents who had used Apple products for at least two months and used various shopping channels (web, application, marketplace, physical stores). Data were analyzed using the Structural Equation Modeling method with the Smart PLS version 4.0 analysis tool. The results of the study showed that direct service quality and omnichannel marketing have a positive and significant effect on customer satisfaction and customer loyalty, customer satisfaction has a positive and significant effect on customer loyalty. In the results of the study, indirectly, service quality and omnichannel marketing have a positive and significant effect on customer loyalty through customer satisfaction.